ANALISIS KEERATAN HUBUNGAN DI ANTARA PELANGGAN – KARYAWAN DAN PERUSAHAAN MENGGUNAKAN METODE HUMAN SIGMA (Studi Kasus : Jeng Dewi Wedding Organizer) - Sunaryo Sunaryo; Abdul Kholid (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
One of the service industry in Indonesia is wedding Organizer. It’s operation is fasilitation in wedding fiesta. To increase the volume of operation, the Jeng Dewi Wedding Organizer has to createsquality of services. It can be done by increasing engagements and relations amongs employeecustomer and the company. Engagement amongs of them will be the main factor of the company’s sucsess. The customers has to be made satisfied by services. They are not satisfied by rational but olso by emotional. The customers which satisfied by services will results a big profit. To do it coompany has to create a big engagements among of them. It needs an analysis, which can use Human Sigma to measure the value of engagement. Human Sigma is a tool to analyse the person’s emotinal . The result of this analysis is 35.5% for the value Human Sigma, 49 % for the value of Customers Engagement and 49 % for the value of Employee Engagement. So the corporation has to increase all of this parameter.